Cash Holding, Financial Leverage, Profitability, Firm Size, Income Smoothing: Moderating Managerial Ownership - Musyafa, Khosyi Anisul; Kholilah, Kholilah (E-Jurnal Akuntansi, 2023)
This study aims to empirically demonstrate the effect of cash holding, financial leverage, profitability, and company size on income smoothing in the Indonesia Stock Exchange's primary consumer goods sector from 2017 to 2021. The study population amounted to 98 companies and a sample of 16 companies. This study used logistic regression analysis and moderation regression analysis for hypothesis testing. The findings revealed that cash holding and leverage negatively affect income smoothing, profitability positively affect income smoothing, whereas company size has no effect. Furthermore, the study's findings empirically demonstrate that leverage strengthens managerial ownership's influence on income smoothing. Keywords: Income Smoothing; Cash Holding; Financial Leverage; Profitability; Firm Size; Managerial Ownership